2019
DOI: 10.2147/ott.s219562
|View full text |Cite
|
Sign up to set email alerts
|

<p>Nitrogen Permease Regulator-Like-2 Exhibited Anti-Tumor Effects And Enhanced The Sensitivity Of Colorectal Cancer Cells To Oxaliplatin And 5-Fluorouracil</p>

Abstract: BackgroundColorectal cancer (CRC) is one of the most common malignant tumors in the world. Our previous study revealed that nitrogen permease regulator-like-2 (NPRL2), a promising anti-tumor gene, was downregulated at both the blood and tissue levels in CRC patients compared with that in healthy individuals.PurposeThis study aims to explore the role of NPRL2 in CRC.MethodsHerein, we constructed NPRL2 overexpression lentivirus vectors and transfected them into HT29 cells. The transfected cells were inoculated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Previous studies reported that NPRL2 is associated with tumor growth in vitro and in vivo in different cancers. [ 21 , 23 , 24 ] However, the study of NPRL2 in hepatocarcinogenesis in vitro or in vivo has not been reported in the literature. Our study demonstrated that the efficient down‐regulation of NPRL2 protein in HCC cells decreased the NPRL2, NPRL3, and DEPDC5 protein levels, promoted cell proliferation, colony formation and migration, and increased HCC tumor growth in the subcutaneous and orthotopic tumor mouse model through the mTOR pathway and regulation of autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that NPRL2 is associated with tumor growth in vitro and in vivo in different cancers. [ 21 , 23 , 24 ] However, the study of NPRL2 in hepatocarcinogenesis in vitro or in vivo has not been reported in the literature. Our study demonstrated that the efficient down‐regulation of NPRL2 protein in HCC cells decreased the NPRL2, NPRL3, and DEPDC5 protein levels, promoted cell proliferation, colony formation and migration, and increased HCC tumor growth in the subcutaneous and orthotopic tumor mouse model through the mTOR pathway and regulation of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 , 19 , 20 ] Several cancers, including breast cancer, ovarian cancer, prostatic cancer, and gastrointestinal stromal tumors, were analyzed and found to be associated with DEPDC5 and NPRL2, but the analysis of NPRL3 remains incomplete. [ 11 , 18 , 19 , 21 , 22 , 23 , 24 ] A previous study showed that high NPRL2 messenger RNA (mRNA) expression significantly reduces the overall survival (OS) of patients with human HCC. [ 25 ] There was a significant association between the DEPDC5 polymorphism and the risk of hepatitis B (HBV) and hepatitis C (HCV)–related HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, our study did not yield positive results in docetaxel, irinotecan, oxaliplatin, and cisplatin due to the small sample size. Previous studies have reported some mechanisms by which NPRL2 affected drug sensitivity (10,12,(52)(53). The overexpression of NPRL2 activated the DNA damage checkpoint pathway to resensitise drugresistant cells to cisplatin treatment (12).…”
Section: Discussionmentioning
confidence: 99%
“…NPRL2 inhibited PDK1 activation through binding to PDK1 and affected downstream molecules to enhance the sensitivity of cancer cells to anticancer drugs (52). NPRL2 also affected the PI3K/Akt/mTOR signalling and inhibited the activation of the multidrug resistance transporter proteins P-gp and MRP1 to reverse 5-fluorouracil resistance in colorectal cancer (10,53). In our study, KEGG analysis also suggested that genes co-expressed with NPRL2 were significantly enriched for genes regulating autophagy, which were essential for the regulation of gastric cancer chemotherapy resistance (41).…”
Section: Discussionmentioning
confidence: 99%
“…For example, missense mutations in metastatic breast cancers are twice more frequent in Nprl2 (1.55%), than in Nprl3 or Depdc5 (0.78%) [196]. Low levels of NPRL2 expression have mostly been detected in solid tumors (Figure 6), including hepatocellular carcinoma [197], glioblastoma [12], as well as in renal [198,199], ovarian [12,199], colorectal [199][200][201][202], breast [199,203] and lung cancers [157,160,199,204,205]. Paradoxically, NPRL2 might also have functions as an oncogene.…”
Section: Cancer and Anticancer Drug Resistance-nprl2 And Othersmentioning
confidence: 99%